Simulator Sickness and Spectacular Destruction: Survival Research Laboratories' Theater of Operations - Mark Dery (Oz, 1994)
The Strategic Air Command in Omaha, Nebraska is closed for business. Described in the December 29, 1991 New York Times as "the nerve center of the United States' nuclear strike force," the SAC once employed 260,000 people at 66 bases; its underground command post incarnated Hollywood visions of cold war paranoia, omniscient computers, and wall-sized maps sprinkled with blinking lights, like the one in Stanley Kubrick's Dr. Strangelove.